Evaluation of the results of surgical treatment of ankle fractures with the tibiofi bular syndesmosis injury - Golovakha, M. L.; Kozhemyaka, М. А.; Maslennikov, S. O.; Головаха, Максим Леонідович; Кожем'яка, Максим Олександрович; Масленніков, Сергій Олегович (ЗДМУ, 2016)
Background. Ankle fractures are the most common injuries among the damages of ankle joint. The most common complication in such fractures is the damage of the tibiofi bular joint, leading to increase in the duration of treatment and adverse outcomes. Despite the large number of publications, the problem of this type injury treatment is far from solving it. The questions remain open regarding the method of surgical treatment and results evaluation. Aim. To evaluate the results of surgical treatment of ankle fractures, complicated with tibiofi bular syndesmosis injury with the help of hardware-bazometric complex and make a comparison with the existing methods of assessment, such as AOFAS and OMAS. Materials and methods. This study presents an analysis of 80 patients with mentioned fractures surgical treatment results. Patients were divided into 2 groups. The fi rst group (44 patients) was treated with the help of tension band wiring for fi xing tibiofi bular syndesmosis in combination with the original extramedullary plate with polyaxial insertion and blocking of screw for osteosynthesis of lateral malleolus fractures. The second group (36 patients) was treated according to the AO technique. The analysis of results was performed in 3, 6 and 12 months after surgery use of scales AOFAS and OMAS, as well as bazometric and stabilometric assessment using “Bazometr” complex. Results. In 3 and 6 months AOFAS and OMAS results corresponded to data of bazometric and stabilometric indicators. The analysis showed the best results among the fi rst group of patients, especially in the early stages. In 12 months the difference between indicators reduced, but remained signifi cantly better in the 1st group. Conclusions. The reported data of clinical observations and their analysis demonstrate the effectiveness of the proposed method of ankle fractures with the tibiofi bular syndesmosis injury surgical treatment
Оцінювання результатів хірургічного лікування переломів кісточок, що ускладнені пошкодженням міжгомілкового синдесмозу
Keywords: Tibiofibular Syndesmosis; Surgical Traumatology; Ankle Fractures; Orthopedic Procedures